Determinantes do aborto provocado entre mulheres admitidas em hospitais em localidade da região Nordeste do Brasil Determinants of iduced abortion among poor women admitted to hospitals in locality of the region northeast Brazil - Walter Fonseca; Chizuru Misago; Luciano L. Correia; João A. M. Parente; Francisco Chagas Oliveira (Universidade de São Paulo, 1996)
Com o objetivo de identificar os determinantes do aborto provocado entre mulheres admitidas por complicações decorrentes dos abortos, nos hospitais-maternidades públicos em Fortaleza, CE (Brasil) foram entrevistadas 4.359 pacientes entre 1º de outubro de 1992 e 30 de setembro de 1993. Os dados foram coletados através de questionário estruturado. São apresentados os determinantes dos abortos provocados em 2.084 (48%) mulheres classificadas como tendo induzido aborto. Dois terços (66%) das mulheres relataram a indução do aborto com o uso isolado do Cytotec(R) (misoprostol) ou associado a outro meio abortivo. Os resultados indicam que, na população estudada, a indução do aborto é prática comum entre jovens, solteiras (ou que vivem sem um parceiro estável), de baixa paridade, com escolaridade incipiente e não-usuárias de métodos contraceptivos. Recomenda-se a realização de estudos que investiguem os conhecimentos relacionados a percepções, conceitos culturais do aborto, e às razões por que mulheres pobres fracassam na adoção de métodos de planejamento familiar. In Brazil, abortion is legally allowed only when it is necessary to save a woman's life or when pregnancy has occurred following rape. Despite this law, iduced abortion is widely carried out. This study presents the findings as to the determinants of 2,084 abortions admitted to two major obstetric hospitals in Fortaleza, Brazil, between October 1992 and September 1993. Most of these women (2,074) have admitted an attempt to terminate pregnancy and 10 women were classified as induced abortion cases based on the findings of signs of intervention such as cervical laceration, perforation or foreign bodies in the vagina or uterus. The study findings indicate that self-administration of medicines plays an important role in terminating pregnancy. Among the 2,074 women who admitted to terminating the pregnancy 66% reported using misoprostol to induce abortion. Misoprostol, a prostaglandin E1 analogue indicated for ulcer treatment, has been widely used as an abortifacient by women in Brazil. Misoprostol has some uterine effects but it is not effec-tive in inducing abortion. Among women who were hospitalized for complications resulting from abortion about 59.7% were 20 to 29 years old and 22.6% were aged less than 20. The majority of the women (91.6%) were Catholic and only 4.3% were illiterate. About 62% of the abortion cases lived alone or did not have a stable partner. Most of the women (59.2%) reported less than 2 live births and 11.8% had experienced a previous abortion; 61.1% of the women were not using a contraceptive method at the time of conception. The main reasons for this were "fear of side effects", "did not expect to have sexual intercourse" and "did not expect to get pregnant". The authors sug-gest that the situation of a high rate of self-inflicted abortion may be changed by the application of an appropriate contraceptive and reproductive health programme.